2017
DOI: 10.1122/1.4990640
|View full text |Cite
|
Sign up to set email alerts
|

An original combined method for electrical conductivity measurement of polymer composites under extensional deformation

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The network destruction is more complex and is intimately linked to the filler network structure. In fact, it has been observed that under shear deformation at large shear rates [16] or under extensional deformation [17], the agglomerates are stretched and orient in the deformation direction. The aggregates network morphology changes in response to strains and, more precisely, its response is linked to its initial morphology [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The network destruction is more complex and is intimately linked to the filler network structure. In fact, it has been observed that under shear deformation at large shear rates [16] or under extensional deformation [17], the agglomerates are stretched and orient in the deformation direction. The aggregates network morphology changes in response to strains and, more precisely, its response is linked to its initial morphology [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] For example, in elongation, the CNTs are strained apart from each other, destructing fillers connections hence triggering a conductor to insulator transition. [ 20 ] Conversely, in the case of shear deformation, both increase and decrease in conductivity can be achieved. During a shear experiment, the effective concentration evolves monotonically depending on the initial network structure and the applied deformation.…”
Section: Description Of the Proposed Modelmentioning
confidence: 99%
“…[ 16 ] Electrical properties rely on a continuous network composed by contacts between small aggregates and individual CNTs. [ 17‐20 ] A contact here is considered an electrical contact, which means an electrical charge transfers between CNT by any mechanism (including tunnel effect). [ 21‐23 ] This complex grid can be modified during processing steps (thermoforming, mold injection, extrusion, and so on) by the applied mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations